Evaluations that Matter : 2016 Annual Report - Independent Evaluation Group (World Bank, Washington, DC, 2021)
In keeping with our goal of informing the World Bank Group's activities and operations with timely, relevant evaluations, IEG refocused its work during the year. We introduced three strategic engagement areas (SEAs)—Inclusive Growth, Sustained Service Delivery for the Poor, and Environmental Sustainability. The strategic engagement areas aim to drive a more selective, coordinated, and focused approach within the organization and to align IEG's evaluation work more closely with the World Bank Group's priorities. The SEAs are also a platform for more effective stakeholder engagement—ensuring that IEG and Bank Group management engagement, for example, is focused on the most critical development challenges. IEG delivered a number of influential products during the year under each of the strategic engagement areas.